2016
DOI: 10.1159/000444179
|View full text |Cite
|
Sign up to set email alerts
|

Early Conventional MRI for Prediction of Neurodevelopmental Impairment in Extremely-Low-Birth-Weight Infants

Abstract: Background: Extremely-low-birth-weight (ELBW; ≤1,000 g) infants are at high risk for neurodevelopmental impairments. Conventional brain MRI at term-equivalent age is increasingly used for prediction of outcomes. However, optimal prediction models remain to be determined, especially for cognitive outcomes. Objective: The aim was to evaluate the accuracy of a data-driven MRI scoring system to predict neurodevelopmental impairments. Methods: 122 ELBW infants had a brain MRI performed at term-equivalent age. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
4
29
2
Order By: Relevance
“…However, lower sensitivity means that some infants with normal MRI may progress to have adverse motor outcomes. This is consistent with studies of MRI at TEA . For determination of a later diagnosis of CP, sensitivity was more frequently higher than specificity, indicating that most infants who progress to CP were identified by abnormalities on MRI.…”
Section: Discussionsupporting
confidence: 85%
“…However, lower sensitivity means that some infants with normal MRI may progress to have adverse motor outcomes. This is consistent with studies of MRI at TEA . For determination of a later diagnosis of CP, sensitivity was more frequently higher than specificity, indicating that most infants who progress to CP were identified by abnormalities on MRI.…”
Section: Discussionsupporting
confidence: 85%
“…Qualitative assessment of the presence of DEHSI exhibits low intra- and inter-rater reliability. 80,81 Even advanced MRI studies are susceptible to such concerns. Several of the advanced MRI studies in this review did not report the reliability of brain measurements and those that did usually did not report more robust measures such as within-subject standard deviation and repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Like WMA, qualitative GMA are usually stratified according to their degree of severity and distribution (cortical, subcortical, and/or cerebellar) ( Inder et al, 2003 , Kidokoro et al, 2013 , Woodward et al, 2006 ). Although GMA in preterm infants have often been associated with PVL, these could be difficult to detect by conventional MRI and, consequently, most neuroradiologists do not report these findings in clinical practice ( Slaughter et al, 2016 ).…”
Section: Neonatal and Pediatric Conventional Neuroimagingmentioning
confidence: 99%
“…Macrostructural and microstructural corpus callosum abnormalities that result from prematurity in very preterm infants also correlated with adverse neurodevelopmental outcomes at 2 years of age measured with the Bayley Scales of Infant Development (BSID-II) ( Thompson et al, 2012 ). On the other hand, GMA have also been associated with language, cognitive and motor delays and cerebral palsy at 18–24 months of age ( Slaughter et al, 2016 , Woodward et al, 2006 ). Omizzolo et al (2014) reported that abnormalities of the basal ganglia and the thalamus in very preterm infants were the strongest predictor of memory and learning performance outcomes at 7 years of age.…”
Section: Neonatal and Pediatric Conventional Neuroimagingmentioning
confidence: 99%